Neurocognitive dysfunction in systemic lupus erythematosus: association with antiphospholipid antibodies, disease activity and chronic damage. - Fabrizio Conti; Cristiano Alessandri; Carlo Perricone; Rossana Scrivo; Soheila Rezai; Fulvia Ceccarelli; Francesca Romana Spinelli; Elena Ortona; Massimo Marianetti; Concetta Mina; Guido Valesini (PLoS ONE, 2012)
INTRODUCTION:Systemic lupus erythematosus (SLE) is characterized by frequent neuropsychiatric involvement, which includes cognitive impairment (CI). We aimed at assessing CI in a cohort of Italian SLE patients by using a wide range of neurocognitive tests specifically designed to evaluate the fronto-subcortical dysfunction. Furthermore, we aimed at testing whether CI in SLE is associated with serum autoantibodies, disease activity and chronic damage. METHODS:Fifty-eight consecutive patients were enrolled. Study protocol included data collection, evaluation of serum levels of ANA, anti-dsDNA, anti-cardiolipin, anti-β(2)-glycoprotein I, anti-P ribosomal, anti-endothelial cell, and anti-Nedd5 antibodies. SLEDAI-2000 and SLICC were used to assess disease activity and chronic damage. Patients were administered a test battery specifically designed to detect fronto-subcortical dysfunction across five domains: memory, attention, abstract reasoning, executive function and visuospatial function. For each patient, the raw scores from each test were compared with published norms, then transformed into Z scores (deviation from normal mean), and finally summed in the Global Cognitive Dysfunction score (GCDs). RESULTS:Nineteen percent of patients had mild GCDs impairment (GCDs 2-3), 7% moderate (GCDs 4-5) and 5% severe (GCDs≥6). The visuospatial domain was the most compromised (MDZs = -0.89±1.23). Anti-cardiolipin IgM levels were associated with visuospatial domain impairment (r = 0.331, P = 0.005). SLEDAI correlated with GCDs, and attentional and executive domains; SLICC correlated with GCDs, and with visuospatial and attentional domains impairment. CONCLUSIONS:Anti-phospholipids, disease activity, and chronic damage are associated with cognitive dysfunction in SLE. The use of a wide spectrum of tests allowed for a better selection of the relevant factors involved in SLE cognitive dysfunction, and standardized neuropsychological testing methods should be used for routine assessment of SLE patients.